2010
DOI: 10.1097/qai.0b013e3181f98628
|View full text |Cite
|
Sign up to set email alerts
|

High Accuracy of Home-Based Community Rapid HIV Testing in Rural Malawi

Abstract: Face-to-face rapid testing by health personnel with minimum training at the client's home performs well when used on a wide scale in the community setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(50 citation statements)
references
References 15 publications
1
49
0
Order By: Relevance
“…Yield of HIV positive individuals (HIV positivity) was reported in 29 home studies 14,15,18,27,2932,34,36,38,41–45,63,65,66,68,7073,88,89 , one home with self-testing 11 , 12 mobile 10,13,68,72,9295,97,98,103,107,114 , five campaign 46,47,76,77,120 , three workplace 79,80,121 , four key population 12,115,116,122 , four index partner 4850,88 , 27 facility VCT 5456,64,81,84,88,9193,95,98,102,104107,114,118120,123127 , and 17 facility PITC 56,57,59,60,81,8388,99,110113,126 studies. Community-based strategies for the general population had lower HIV positivity (6–11%) than facility HTC (18–20%), whereas targeted community HTC for key populations and sexual partners of index patients had the highest HIV yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Yield of HIV positive individuals (HIV positivity) was reported in 29 home studies 14,15,18,27,2932,34,36,38,41–45,63,65,66,68,7073,88,89 , one home with self-testing 11 , 12 mobile 10,13,68,72,9295,97,98,103,107,114 , five campaign 46,47,76,77,120 , three workplace 79,80,121 , four key population 12,115,116,122 , four index partner 4850,88 , 27 facility VCT 5456,64,81,84,88,9193,95,98,102,104107,114,118120,123127 , and 17 facility PITC 56,57,59,60,81,8388,99,110113,126 studies. Community-based strategies for the general population had lower HIV positivity (6–11%) than facility HTC (18–20%), whereas targeted community HTC for key populations and sexual partners of index patients had the highest HIV yield (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies of RDT performance in both community- and health facility-based HIV testing have reported higher sensitivities than observed in our study. Molesworth et al found a sensitivity of 99% comparing third-generation RDT kits with third-generation EIA during HIV testing in the context of a household survey, using initially two RDTs in parallel with a tiebreaker, then two RDTs in series with a tiebreaker and finally retesting all positives and 10% of the negatives in the laboratory [22]. Jackson et al found a sensitivity of 98% in a community randomized controlled trial of home-based HCT conducted by lay counsellors again comparing third-generation RDT kits with a third-generation EIA [23].…”
Section: Discussionmentioning
confidence: 99%
“…20,21 We searched Pubmed and EMBASE for community-based HTC studies published between January 1 st , 2000, and June 12th, 2014, with the terms HIV and Africa South of the Sahara and (mass screening OR testing OR screen OR diagnosis OR counseling). We identified 1,004 abstracts for review, including two recent systematic reviews.…”
Section: Research In Contextmentioning
confidence: 99%
“…16 Community-based HTC strategies include community campaigns, 17 which achieve large numbers of testing in a short period, and home HTC, 18,19 through which HIV counseling and testing is provided by lay counselors in homes. 20,21 Systematic reviews found that community-based HTC, 16 including home HTC, 19 were acceptable and resulted in high uptake of testing. In addition, studies have demonstrated high linkage to care 16 and viral suppression over 6 months.…”
Section: Introductionmentioning
confidence: 99%